Dentigerous cyst in mandible: case report (Research, Society and Development, 2021)
The dentigerous cyst is identified as a cavity lined with odontogenic epithelium that surrounds the crown of an impacted tooth, located mainly in the mandible and in the region of the lower third molar. Its formation occurs due to the accumulation of fluid, caused by the pressure exerted on the follicle, by a tooth that tries to erupt. It is more common in individuals between 10 and 30 years of age, with a preference for male patients. The lesion is usually asymptomatic, being discovered on routine radiographic examinations. Radiographically, a well-defined radiolucent area associated with the crown of an impacted tooth is observed. Treatment options are enucleation, marsupialization, and decompression followed by enucleation. The initial diagnosis hypotheses were dentigerous cyst, keratocyst or unicystic ameloblastoma. The objective of this work is to present a clinical case, of a female patient, 32 years old, black, who presented a dentigerous cyst of great extension associated to the tooth 38 included. The treatment option addressed was according to the characteristics of the lesions, enucleation was instituted with removal of the involved element and clinical follow-up with radiographic exams. It was concluded that, given the high frequency, it is essential for the dentist to know the clinical and radiographic characteristics of the dentigerous cyst so that they can be properly diagnosed and treated. Radiographic follow-up reveals complete local bone neoformation, with no sign of lesion recurrence.